Shifting Values in Global Children’s Literature: A Comparative Thematic Analysis from 2001 to 2025 - Desy Eva Laila Rokhmah; Abdurrahman Shaleh Reliubun; Arin Mantara Anggawirya; Reski Amalia S (Hasanuddin University, 2026)
Children’s literature reflects how societies teach younger generations moral reasoning, empathy, and cultural identity. Over the past two decades, global children’s literature has undergone significant shifts in theme and form, reflecting broader social and technological changes. This study examines the evolution of ethical functions, representation, and narrative media in children’s literature across three phases: 2001–2009, 2010–2019, and 2020–2025. Using a qualitative comparative design and reflexive thematic analysis, the research examines award-winning and internationally circulated works to identify shifting values and patterns in storytelling practices. Findings indicate that the literary works of the early 2000s, dominated by fantasy and dystopia, deliver the moral laboratories where young readers practiced ethical judgment within imagined worlds. The 2010s redirected this focus toward realism, inclusion, and social participation, highlighting the rise of own-voices authors and multimodal formats such as verse and graphic novels. In the 2020s, children's literature has increasingly engaged with real-world crises—pandemics, racial justice, climate anxiety, and mental health—transforming stories into tools for recovery, empathy, and digital literacy. Across these three periods, children’s literature moves from imagining moral choices to enabling real ethical action, from representing diversity to institutionalizing it, and from textual storytelling to interactive, cross-media experiences. This evolution demonstrates that children’s literature is no longer a passive reflection of cultural change but actively shapes global empathy and civic awareness among young readers.